Clinical assessment of absence of palmaris longus muscle and its association with ethnicity - Quratulain Javaid; Ambreen Usmani; Ambreen Surti (Journal of the Pakistan Medical Association, 2023)
Objective: To compare two clinical tests used for assessment of absence of palmaris longus, and to determine the prevalence of absence of palmaris longus among ethnic groups in a cosmopolitan setting. Method: The cross-sectional descriptive study was conducted at the Bahria University Health Sciences, Karachi, from April 2021 to May 2022, during which forearms belonging to Sindhi, Punjabi and Urdu-speaking ethnic groups were tested. Assessment of presence or absence of palmaris longus was performed using Schaeffer’s and Thompson’s tests. Agenesis and association of ethnicity and agenesis were compared. Data was analysed using SPSS 23. Results: Of the 250 subjects, 152(60.8%) were females and 98(39.2%) were males. The overall mean age was 20.4±2.23 years (range: 18-23 years). In terms of ethnicity, 100(40%) subjects each were Punjabis and Urdu-speaking, while 50(20%) were Sindhis. The total forearms assessed were 500. The overall agenesis was 186(37.2%). When the two assessment tests were compared, highly significant differences were noted (p<0.000). Overall agenesis was highest among Sindhis 40%, followed by 38% in Punjabis, and 35% in Urdu-speaking. Significant differences were observed when one-sided palmaris longus absence was compared with two-sided absence (p<0.037). Conclusion: Schaeffer’s test had more accuracy compared to the Thompson’s test in the determination of palmaris longus agenesis. There were variations in terms of agenesis among the ethnic groups. Key Words: Clinical assessment, Aabsence, Palmaris longus, Association, Ethnicity.